Soil microbial fuel cell based self-powered cathodic biosensor for sensitive detection of heavy metals - Wang, Shi-Hang; Wang, Jian-Wei; Zhao, Li-Ting; Abbas, Syed Zaghum; Yang, Zhugen; Yong, Yang-Chun (MDPI, 2023)
Soil microbial fuel cells (SMFCs) are an innovative device for soil-powered biosensors. However, the traditional SMFC sensors relied on anodic biosensing which might be unstable for long-term and continuous monitoring of toxic pollutants. Here, a carbon-felt-based cathodic SMFC biosensor was developed and applied for soil-powered long-term sensing of heavy metal ions. The SMFC-based biosensor generated output voltage about 400 mV with the external load of 1000 Ω. Upon the injection of metal ions, the voltage of the SMFC was increased sharply and quickly reached a stable output within 2~5 min. The metal ions of Cd2+, Zn2+, Pb2+, or Hg2+ ranging from 0.5 to 30 mg/L could be quantified by using this SMFC biosensor. As the anode was immersed in the deep soil, this SMFC-based biosensor was able to monitor efficiently for four months under repeated metal ions detection without significant decrease on the output voltage. This finding demonstrated the clear potential of the cathodic SMFC biosensor, which can be further implemented as a low-cost self-powered biosensor.
Keywords: soil microbial fuel cells; heavy metals; biosensors; soil pollution